2004
DOI: 10.1002/ejic.200300935
|View full text |Cite
|
Sign up to set email alerts
|

Metal Telluride Clusters — From Small Molecules to Polyhedral Structures

Abstract: 2− ion. Ligand cross-transfer (CO versus Te) from one metal center to the other and subsequent charge separation lead to the formation of anionic metal telluride clusters and cationic carbonylniobocene species. The latter play a decisive role in tuning the electronic properties of the cluster

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 91 publications
(66 reference statements)
0
12
0
Order By: Relevance
“…The importance of hydrogen-bonding acceptor CO ligands for the crystal packing has already been discussed [15,16], and in our case it may be increased by electrostatic forces. The role of large organometallic cations for the stabilization of anionic metal telluride clusters has already been mentioned [1]. The formation of the [Cp′ 4 Nb 2 Te 2 CH 3 ] + cation cannot yet be explained and is therefore the subject of further investigations.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The importance of hydrogen-bonding acceptor CO ligands for the crystal packing has already been discussed [15,16], and in our case it may be increased by electrostatic forces. The role of large organometallic cations for the stabilization of anionic metal telluride clusters has already been mentioned [1]. The formation of the [Cp′ 4 Nb 2 Te 2 CH 3 ] + cation cannot yet be explained and is therefore the subject of further investigations.…”
Section: Resultsmentioning
confidence: 96%
“…Transition metal telluride complexes bearing niobocene fragments are useful reagents for the synthesis of heterometallic telluride complexes and metal telluride clusters when reacting with binary transition metal carbonyls [1]. The main strategy in this chemistry uses a ligand cross-transfer (CO versus Te) from one metal center to the other.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, comparatively little is known about palladium telluride complexes [4]. We have recently shown that use of ½Cp à 2 NbðTe 2 HÞ as tellurium transfer reagent [5] in the reaction with [Ni(COD) 2 ] in the presence of Ph 2 PCH 2 PPh 2 (dppm) provides access to the mixed early-late transition metal clusters ½ðCp à 2 NbÞ 2 NiTe 4 and [(Cp * Nb) 2 Ni 5-Te 7 (dppm) 2 ] [6]. Of particular interest for us has been the electronic structure of the tetratelluronickelate cluster.…”
Section: Introductionmentioning
confidence: 93%
“…This complex contains the hitherto unknown [WTe 4 ] 2– moiety 6. The versatile abilities of [Cp* 2 NbTe 2 H] ( 1 ) and 2 to serve as tellurium transfer reagents towards transition metal carbonyls has already been reviewed 7. In this work, we report on the reactions of 1 and 2 with [Ni(COD) 2 ] in the presence of Ph 2 PCH 2 PPh 2 (dppm).…”
Section: Introductionmentioning
confidence: 98%